2003
DOI: 10.1007/s00268-003-6693-5
|View full text |Cite
|
Sign up to set email alerts
|

Role of Somatostatin in the Prevention of Pancreatic Stump‐related Morbidity following Elective Pancreaticoduodenectomy in High‐risk Patients and Elimination of Surgeon‐related Factors: Prospective, Randomized, Controlled Trial

Abstract: A prospective, randomized, controlled trial was performed to determine the efficacy of somatostatin in the prevention of pancreatic stump-related complications with elimination of surgeon-related factors in high-risk patients undergoing pancreaticoduodenectomy. From August 1997 to December 2000, 54 patients, 28 men and 26 women, with age ranged from 32 to 89 years, were randomly assigned to somatostatin group ( n = 27) or placebo group ( n = 27). Ninety-four percent of the patients had pancreatic and periampul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 37 publications
1
66
0
2
Order By: Relevance
“…Unfortunately, a subgroup meta-analysis of high-risk patients cannot be performed because of limited data. However, the studies of Lowy et al [39], Yeo et al [43], and Shan et al [41] showed that SAs could not reduce the rate of PF and other complications in patients at high-risk after PD. In addition, Fernández-Cruz et al [33] further demonstrated no significant differences in median pancreatic juice output were found between SAs and placebo groups in high-risk patients (with a pancreatic duct diameter <5 mm).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, a subgroup meta-analysis of high-risk patients cannot be performed because of limited data. However, the studies of Lowy et al [39], Yeo et al [43], and Shan et al [41] showed that SAs could not reduce the rate of PF and other complications in patients at high-risk after PD. In addition, Fernández-Cruz et al [33] further demonstrated no significant differences in median pancreatic juice output were found between SAs and placebo groups in high-risk patients (with a pancreatic duct diameter <5 mm).…”
Section: Discussionmentioning
confidence: 99%
“…Of the 25 potentially appropriate studies [20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44] seven were excluded for reporting no explicit outcome of PD [20,21,22,23,24,25,27] one for duplicate publication [26] one for comparing somatostatin with octreotide [29] one for using octreotide in the control group [28]. Finally, 15 RCTs were included in the meta-analysis (table 1) [30,31,32,33,34,35,36,37,38,39,40,41,42,43,44]. …”
Section: Resultsmentioning
confidence: 99%
“…It reduces gastrointestinal exocrine and endocrine secretions. Randomized control studies have shown conflicting evidence regarding its use for reducing the incidence of developing pancreatic fistulas [10][11][12]. Much of the promising results were seen in high risk patients.…”
Section: Discussionmentioning
confidence: 99%
“…This includes parenteral nutrition (PN) while resting the bowel, drainage of collections, antibiotics and use of octeotride. However clinical trials have shown conflicting evidence regarding the use of octreotide in managing pancreatic fistulas [10][11][12]. Those which show resistant to healing will need interventions [1].…”
Section: Introductionmentioning
confidence: 99%
“…Table 4 summarizes RCTs regarding the administration of somatostatin and somatostatin analogues after pancreatic surgery. Two RCTs reported that prophylactic somatostatin or octreotide significantly reduced the incidence of pancreatic fistula after PPPD (39,40). On the other hand, four recent RCTs reported that the use of somatostatin analogues including octreotide and vapreotide, did not reduce pancreatic fistula after pancreas surgery (41)(42)(43)(44)(45).…”
Section: Pancreatic Duct Stent In Pjmentioning
confidence: 99%